2022
DOI: 10.1161/atvbaha.122.318158
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA TPRG1-AS1 Suppresses Migration of Vascular Smooth Muscle Cells and Attenuates Atherogenesis via Interacting With MYH9 Protein

Abstract: BACKGROUND: Migration of human aortic smooth muscle cells (HASMCs) contributes to the pathogenesis of atherosclerosis. This study aims to functionally characterize long noncoding RNA TPRG1-AS1 (tumor protein p63 regulated 1, antisense 1) in HASMCs and reveal the underlying mechanism of TPRG1-AS1 in HASMCs migration, neointima formation, and subsequent atherosclerosis. METHODS: The expression of TPRG1-AS1 in atherosclerotic plaques was verified a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…24 Additionally, estrogen has an inhibitory effect on diet-induced atherosclerosis formation. [25][26][27] Therefore, to accelerate lesion formation, only male animals were used in our study. To establish atherosclerotic lesions, 6-to 8-week-old male ApoE −/− , ApoE −/− NEAT1 −/− , and ApoE −/− METTL14 +/− mice were fed a high-fat diet (HFD) containing 10% lard, 4% milk powder, 2% cholesterol, and 0.5% sodium cholate for 12 weeks.…”
Section: Animalsmentioning
confidence: 99%
“…24 Additionally, estrogen has an inhibitory effect on diet-induced atherosclerosis formation. [25][26][27] Therefore, to accelerate lesion formation, only male animals were used in our study. To establish atherosclerotic lesions, 6-to 8-week-old male ApoE −/− , ApoE −/− NEAT1 −/− , and ApoE −/− METTL14 +/− mice were fed a high-fat diet (HFD) containing 10% lard, 4% milk powder, 2% cholesterol, and 0.5% sodium cholate for 12 weeks.…”
Section: Animalsmentioning
confidence: 99%
“…MAP7D2 interacts with the MYH9 protein to protect it from ubiquitin-mediated degradation, subsequently reducing the secretion of HMGB1 to inhibit the infiltration of CD8 + cytotoxic T lymphocytes in microsatellite-stable colorectal cancer [ 54 ]. Conversely, the lncRNA TPRG1-AS1 directly interacts with MYH9 to promote its degradation through the proteasome pathway, subsequently hindering F-actin stress fiber formation and finally inhibiting the migration of human aortic smooth muscle cells [ 55 ]. In this study, we found that the proteasomal noncatalytic subunit PSMD2 interacted with MYH9 and induced its degradation via the ubiquitin-proteasome pathway in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Relative protein levels were presented as percent lesion area: relative protein levels (%)=([positive protein in mm 2 /atherosclerotic lesion in mm 2 )×100). 33…”
Section: Methodsmentioning
confidence: 99%
“…Relative protein levels were presented as percent lesion area: relative protein levels (%)=([positive protein in mm 2 /atherosclerotic lesion in mm 2 )×100). 33 Masson staining was performed using a Modified Masson's Trichrome Stain Kit (Solarbio, China), and the mean area of the 6 sections/mouse was used for comparing among groups.…”
Section: Atherosclerosis Analysismentioning
confidence: 99%